Synthesis and Biological Screening of Lupeol-benzylidine Derivatives - Rao, Devendra S.; Parimi, Uma D.; Rao, Nageswara B.; Rao, Karteek A. (Natural Products Journal, The, 2018)
Background: Lupeol, a pentacyclic triterpenoid is found in the stem-bark of Walsura trifoliate. Derivatives of lupeol are associated with a broad range of biological activities. Objective: To synthesis a series of Lupeol-benzylidine derivatives and evaluate their antimicrobial and antiproliferative acitivities. Method: Lupeol was isolated from the bark of Walsura trifoliate. The ring A at C2 position of Lupeol was modified by claisens Schmidt condentation to produce Lupeol-benzylidine derivatives. Antimicrobial assay was performed by broth dilution technique. Results: All the structures were confirmed by 1HNMR, 13CNMR and IR spectroscopic techniques. Compounds 3c and 3h exhibited the highest activity. Conclusion: In conclusion, a series of different benzylidine derivatives from natural product Lupeol have been synthesized. All the tested compounds are found to be as antimicrobial and antiproliferative agents.
Keywords: claisens condensation